Early intervention for heterotopic caesarean scar pregnancy to preserve intrauterine pregnancy may improve outcomes: a retrospective cohort study. Issue 2 (August 2020) - Wang, Yang; Niu, Ziru; Tao, Liyuan; Yang, Yan; Ma, Caihong; Li, Rong
Abstract: Research question: What is the best intervention time and method for patients who are diagnosed with heterotopic caesarean scar pregnancy (HCSP) wishing to preserve intrauterine pregnancy. Design: Four patients diagnosed with HCSP from January 2014 to May 2019 were enrolled. Because HCSP is rare, data on 27 published cases were extracted to augment the analysis. Clinical characteristics and medical documents related to fetal reduction and subsequent maternal–neonate outcomes were analysed. Results: The intervention time was significantly earlier in the full-term birth group (6.76 ± 1.05 weeks) compared with pre-term birth group (8.02 ± 1.55 weeks; P  = 0.042). The cumulative full-term delivery rate was 91.48% when the intervention was at 6 weeks' gestation and decreased to 42.02% at 8 weeks. The maternal–neonate outcome was similar among the selective fetal reduction and surgical removal groups as was delivery time (34.68 ± 3.12 versus 34.80 ± 6.64 weeks; P  = 0.955). In the four cases undergoing selective fetal reduction, the residual mass grew by 1.16–7.07 times compared with the area before reduction. The maximum size of the residual mass was observed at 12–13 weeks and 22–25 weeks. Conclusions: Most patients with HCSP who choose to keep intrauterine pregnancy will be able to carry the fetus to term. Selective fetal reduction would be the first intervention of choice and should take place immediately after diagnosis. The residual mass after reduction could continue to grow throughout the whole pregnancy, although this should not be considered as an indication for termination. With good supervision and careful management, the pregnancy could be maintained and carried to term.